Designing Superoxide-Generating Quantum Dots for Selective Light-Activated Nanotherapy - Goodman, Samuel M.; Levy, Max; Li, Fei-Fei; Ding, Yuchen; Courtney, Colleen M.; Chowdhury, Partha P.; Erbse, Annette; Chatterjee, Anushree; Nagpal, Prashant (Frontiers in Chemistry, 2018)
The rapid emergence of superbugs or multi-drug resistant (MDR) organisms has prompted a search for novel antibiotics, beyond traditional small-molecule therapies. Nanotherapeutics are being investigated as alternatives, and recently superoxide-generating quantum dots (QDs) have been shown as important candidates for selective light-activated therapy and potentiating existing antibiotics against MDR superbugs. Their therapeutic action is selective, can be tailored by simply changing their quantum-confined conduction-valence bands and their alignment with different redox half-reactions, and hence their ability to generate specific radical species in biological media. Here, we show the design of superoxide-generating QDs using optimal QD material and size well matched to superoxide redox potential, charged ligands to modulate their uptake in cells and selective redox interventions, and core/shell structures to improve their stability for therapeutic action. We show that cadmium telluride (CdTe) QDs with conduction band position at -0.5V with respect to Normal Hydrogen Electron (NHE) and visible 2.4 eV bandgap generate a large flux of selective superoxide radicals, thereby demonstrating the most effective light-activated therapy. Although the positively charged QDs demonstrate large cellular uptake, they bind indiscriminately to cell surfaces and cause non-selective cell death, while negatively charged and zwitterionic QD ligands reduce the uptake and allow selective therapeutic action via interaction with redox species. The stability of designed QDs in biologically-relevant media increases with the formation of core-shell QD structures, but an appropriate design of core-shell structures is needed to minimize any reduction in charge injection efficiency to adsorbed oxygen molecules (to form superoxide) and maintain similar quantitative generation of tailored redox species, as measured using electron paramagnetic resonance (EPR) spectroscopy and electrochemical impedance spectroscopy. Using these findings, we demonstrate the rational design of QDs as selective therapeutic kills more than 99% of priority class I pathogens, thus providing an effective therapy against MDR superbugs.